The impact of pre-marital sex ratios on household saving in two Asian countries: The competitive saving motive revisited - Charles Yuji Horioka; Akiko Terada Hagiwara (Osaka University, Institute of Social and Economic Research (ISER), 2016)
This paper estimates a household saving rate equation for India and Korea using long-term time series data for the 1975-2010 period, focusing in particular on the impact of the pre-marital sex ratio on the household saving rate. To summarize the main findings of the paper, it finds that the pre-marital sex (or gender) ratio (the ratio of males to females) has a significant impact on the household saving rate in both India and Korea, even after controlling for the usual suspects such as the aged and youth dependency ratios and income. It has a negative impact in India, where the bride's side has to pay substantial dowries to the groom's side at marriage, but a positive impact in Korea, where, as in China, the groom's side has to bear a disproportionate share of marriage-related expenses including purchasing a house or condominium for the newlywed couple.
Keywords: D12; D14; D91; E21; J11; J12; O16; 330; Age structure of the population; competitive saving motive; dowries; gender ratio; household saving rate; life cycle hypothesis; marriage expenses; pre-marital sex ratio; population control; saving for education; saving for marriage; saving rate; sex ratio; son preference; wedding expenses; Korea; India